Tax Preferences in the Development of Renewable Energy Sources on the Example of a Property Tax in Poland - Damian PRONIEWSKI (Communications of International Proceedings, 2025)
The article addresses the European Union’s climate and energy policy in the area of renewable energy development. One of the legal instruments supporting the development of these sources is an exemption from a property tax, the structure and characteristics of which are analyzed in the framework of local government fiscal policy. The aim of the elaboration is to characterize it as a preferential instrument for the development of renewable energy sources in the light of local government resolutions. Property tax exemptions vary depending on political, economic, environmental and social conditions, as well as local development policy. In the work mainly the dogmatic-legal method has been used with the indication of case studies.
Keywords: Directive (EU) 2023/2413; European Union climate and energy policy; renewable energy sources; exemption from a property tax